Monitoring ultrafast intramolecular proton transfer processes in an unsymmetric β-diketone1. Issue 13 (7th April 2015) - Verma, Pramod Kumar; Steinbacher, Andreas; Koch, Federico; Nuernberger, Patrick; Brixner, Tobias
<x xml:space="preserve">Abstract</x> Electronic excitation of a UV-absorbing unsymmetric β-diketone discloses intramolecular proton transfer among electronic ground as well as excited states.